ANALYSIS OF KOPI KENANGAN: THE CULTURES AND IMPACT ON UNIVERSITAS NEGERI MEDAN STUDENTS - Elisabeth Monica Hutahaean; Stevhany Christiani Siahaan; Rifana Dwi Dywanti Hasibuan; Satyawan Reinhard Stanislaus Lumbantobing (INJOSEDU: International Journal of Social and Education, 2025)
This study delves into the discourse surrounding coffee consumption patterns among teenagers, aiming to understand the social, cultural, and behavioral dimensions of this phenomenon. Employing discourse analysis as the primary methodological framework, the research examines both qualitative and quantitative data gathered from social media platforms, focus groups, and surveys. The findings reveal that coffee consumption among teenagers is not merely a dietary habit but a complex social practice intertwined with identity formation, peer influence, and lifestyle aspirations. The discourse analysis uncovers recurring themes such as the perception of coffee as a symbol of maturity, a tool for social bonding, and a means of managing academic pressures. Additionally, the study highlights the role of marketing and media in shaping teenagers' coffee-related attitudes and behaviors. This comprehensive analysis provides valuable insights into the broader implications of teenage coffee consumption, offering a nuanced understanding of how young people navigate their social worlds through everyday practices like drinking coffee. The implications for health education, marketing strategies, and future research directions are also discussed.